Socio-Demographic Characterstics Of Alleged Sexual Assault (Rape) Cases In Dhaka City - Al-Azad, MAS; Raman, Z; Ahmad, M; Wahab, MA; Ali, M; Khalil, MI (Journal of Armed Forces Medical College, Bangladesh, 2012)
Introduction: Offence means any act of omission made punishable by law for the time being in force. Sexual assault is defined as sexual intercourse performed in a way which is against the provision of the law of the land. Of all the crimes sex related crimes are the most barbarous and humiliating. Rape is the most serious sexual offence, still carrying the death penalty in some parts of the world. Rape is said when 'unlawful sexual intercourse by a man with a woman, by force, fear or fraud'. Young girls and children remain the most vulnerable group to this crime. The alarming rise in the rate of sexual assault worldwide represents a major public health problem. Objectives: To determine socio-demographic characteristics of alleged sexual assault cases in Dhaka city and to create public awareness of furious crime. Methods: The study was conducted on 230 female sexually assaulted victims who reported Dhaka Medical College (DMC) for medical examination during the period between January 2006 and December 2006. Details pertaining to age, sex, religion, literacy, socioeconomic status, site of incidence, time interval between incidence and medical examination, number of assailants, relationship with assailants, findings of physical or genital examination and results of evidence collected during examination were noted. Results: It was revealed from the findings that among 230 female sexually assaulted victims 69.57% were in 11-20 years age group and 11.30% in 21-30 years of age group. Over three-fourths (76.08%) of the victims were Muslims, 78.69% were unmarried, 32.18% were less educated and 77.89 % were with poor socioeconomic background. The majority of the victims (43.91%) knew the assailants and in 30.43% cases they were close friends. Most of the incidents (36.95%) occurred in victim's house followed by Boys' hostel (31.30%). A total 89 victims (38.69%) were examined on the day of the incident. Ninety one (39.57%) victims were found with genital injuries and 83 victims (36.09%) had extra genital injuries and rupture of hymen was found in 78 (33.91%) victims at 6 o'clock position. Conclusion: The study findings may be helpful for baseline information and would be beneficial to the policymakers and programme planners to make awareness among the people. DOI: http://dx.doi.org/10.3329/jafmc.v7i2.10391 JAFMC 2011; 7(2): 21-24